The Shadow Diplomacy and National Security (Turkey as a Model in 2017 and Beyond) (قضايا سياسية, 2024)
Due to the importance of international relations, the escalation of crises, and the intertwining of interests in the international community, and the urgent need to negotiate within a narrow circle surrounded by secrecy and confidentiality in most cases, the concept of shadow diplomacy emerged, which is a relatively modern concept that was used in many American press reports during the rule of US President Donald Trump from 2017 to 2021, where the responsibility of this concept is determined by negotiating to resolve a specific and complex crisis facing the political system within the framework of international relations, such as preventing the outbreak of armed conflict and limiting its spread, or conveying talking points regarding some of the problems surrounding the position of the political system on a specific issue, and this task is often assigned to highly important and professional figures within the National Security Administration, and they are special envoys trusted by their governments to the relevant parties, countries or organizations, in specific and sensitive tasks that are mostly characterized by secrecy and confidentiality, and these tasks carry the characteristic of special and specific importance.